Chatbot for Health Care: A Narrative Review - Syed Azlan Abbas (18472489) (2024)
Background A chatbot is a software designed to simulate human conversation using voice or text as inputs. In medicine and health care, it is used for communication and human-like knowledge transfer as chatbots can manage complex dialogue and conversational flexibility.1,2 A narrative review was performed on chatbot technology to assess current healthcare applications and recent advances in relation to patient support, health promotion, diagnosis, and treatment. Methods An online literature search covering the last two decades was performed using PubMed, Google Scholar, and Web of Science. Quality screening was done and based on the study question; 35 clinical research articles were included. Conclusion Chatbots have shown positive outcomes in various aspects of healthcare and may substantially improve patient safety and quality of life, reduce diagnostic time, and improve accuracy in diagnosis and management. Nevertheless, the role of humans in health care is unsurpassable. Results Chatbots have a role in radio-diagnosis, helping in quick diagnosis and avoids manual delays in reporting. They have shown promising results in self-monitoring for patients which aids in reducing complications. Chatbots are helpful for physicians in treatment planning. They assist patients treat common ailments without medical consultation. Some of the apps provide information about drugs that are contraindicated in lactation and pregnancy. In the past, the implementation of chatbots for cancer patient support has been studied with a good outcome. Chatbots have shown promising results in health promotion. Hitherto, they have been used for the promotion of physical health, adolescent health, sexual health, mental health etc., and have shown promising results. Few studies have revealed their utility in promoting vaccination during the SARS-COV-2 pandemic. Chatbots have the potential to be integrated into clinical practice by working alongside health practitioners to reduce costs, refine workflow efficiencies, and improve patient outcomes (Table 1, Figure 1). Additional institutions affiliated with: Delhi Public School-Modern Indian School, Qatar